Comparison of two ophthalmic solutions of olopatadine hydrochloride (0.1%) and epinastine hydrochloride (0.05%) on clinical signs of vernal keratoconjunctivitis and side effects of the two drugs - Ansari, Tahir Husain; Rizvi, Yusuf (International Journal of Research in Medical Sciences, 2020)
Background: Vernal keratoconjunctivitis (VKC) is a recurrent, bilateral, external, ocular inflammation primarily affecting young adults living in warm dry climates. The objectives of the research was to compare the two ophthalmic solutions of olopatadine hydrochloride (0.1%) and epinastine hydrochloride (0.05%) on clinical signs of vernal keratoconjuntivitis and to determine side effects of both the drugs. Methods: The study was carried out in 40 patients who attended the out-patient department (OPD) Ophthalmology, Darbhanga Medical College and Hospital, Laheriasarai from July 2007 to December 2008. Forty patients with symptoms of VKC (ocular itching, ropy discharge, papillary hypertrophy, gelatinous thickening and horner-trantas spots were selected and included in our study. Results: Mean score of palpebral hyperemia at 0, 14, 28 and 42 days in olopatadine treated eye were 2.1, 1.4, 0.8 and 0.4 respectively having p value <0.01, and <0.01 and <0.05 respectively, while mean score at same stages in placebo eye were 2.1, 2, 1.9, and 1.5 having value >0.05. Epinastine treated group mean score of palpebral hyperemia were <0.01 and <0.01 respectively in epinastine treated eye whereas in placebo treated eye, mean score were 2.1, 2.0, 1.8 and 1.6 respectively having p value >0.05 in all stages. Statistically insignificant reduction at day 14 while very significant reduction at day 28 and 42 was observed in epinastine treated eye as compared to placebo. Conclusions: The present study had shown that both olopatadine and epinastine were effective in treating clinical signs of VKC as compared to placebo.